Topical antifungal bigels: Formulation, characterization and evaluation - Mazurkeviciute Agne; Ramanauskiene Kristina; Ivaskiene Marija; Grigonis Aidas; Briedis Vitalis (Acta Pharmaceutica)
Bigels with antifungal substances, ciclopirox olamine and terbinafine hydrochloride, were made of hydrogel (poloxamer 407 gel) and oleogel (polyethylene and liquid paraffin mixture). Prepared bigels were found physically stable at room temperature for six months and at least four months at 40 °C. Released amount of drug decreased when oleogel concentration in the formulation increased. Release test results depended on the insertion place of active substances. The amount of released substance was highest when ciclopirox olamine was incorporated in both phases in an equal quantity, and terbinafine hydrochloride in oleogel or in hydrogel. All formulations showed great inhibition of Microsporum canis. Thus, bigels with ciclopirox olamine and terbinafine hydrochloride are a promising dosage form for topical use.